2022
DOI: 10.1021/acs.jafc.2c00756
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Juice Industry Wastes as a Source of Bioactives

Abstract: Food processing sustainability, as well as waste minimization, are key concerns for the modern food industry. A significant amount of waste is generated by the fruit juice industry each year. In addition to the economic losses caused by the removal of these wastes, its impact on the environment is undeniable. Therefore, researchers have focused on recovering the bioactive components from fruit juice processing, in which a great number of phytochemicals still exist in the agro-industrial wastes, to help minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 309 publications
(461 reference statements)
0
24
0
1
Order By: Relevance
“…Indeed, a plethora of studies have evaluated the potential to extract many different valuable bioactive compounds from OPW, including essential oils, pectin, and carotenoids. Specifically, other bioconversion technologies or additive manufacturing techniques have also been explored to convert OPW into biochemicals, biopolysaccharides, and bioenergy [ 3 , 15 , 24 , 34 ]. More recently, due to advancement of additive manufacturing techniques, other food products or food wastes including OPW may be explored to create 3D printed food [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a plethora of studies have evaluated the potential to extract many different valuable bioactive compounds from OPW, including essential oils, pectin, and carotenoids. Specifically, other bioconversion technologies or additive manufacturing techniques have also been explored to convert OPW into biochemicals, biopolysaccharides, and bioenergy [ 3 , 15 , 24 , 34 ]. More recently, due to advancement of additive manufacturing techniques, other food products or food wastes including OPW may be explored to create 3D printed food [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that oxidative stress and inflammation are common features reported in endothelial dysfunction, a critical and initiating factor for several vascular complications [ 10 , 11 , 12 , 13 ], flavonoids are widely considered as potential sources of natural product to exert beneficial effects on the cardiovascular system [ 14 ]. Indeed, several previous studies have shown that flavonoids present in orange peel waste (OPW) possessed antioxidant and anti-inflammatory properties [ 15 , 16 ] although less is known on the effects of OPW in endothelial cells. As the OPW represents a considerable proportion of the fruit, abundant in flavonoid content and yet often unconsumed and discarded, it creates an opportunity to explore suitable extraction methods to upcycle these OPW into functional food products or incorporated in drug delivery devices [ 17 ] with potential bioactive properties for enhancing vascular health in animal models [ 18 ] or 3D printed biofabricated models [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leading area of fruit production around the world is citrus cultivation, with its over-production having been transformed with technology into other food products, such as jams and juices. However, these citrus fruit industries produce close to 120 million tons per year of citrus waste worldwide [ 1 , 2 ]. The waste can be seeds, pulp residues, and citrus peels which can cause environmental pollution [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the bioactive compounds present in the wastes produced during the fruit juice industry production are reviewed, updating the extraction techniques and recent valorization approaches. 4 The bioactive compounds from honeybee production byproducts and beekeeping, 5 the soybean processing residues, such as okara, as an excellent source of isoflavones, saponins, and fiber, focusing on the extraction methods and pharmacotherapeutic effects, 6 and the grape winemaking residues from different cultivars 7 are also described. The extraction of pigments, betalains, anthocyanins, chlorophylls, and carotenoids with coloring and health effects from fruit and vegetable byproducts is also reviewed, with an updated description of the methods for their extraction from the agri-food industry.…”
mentioning
confidence: 99%
“…Several reviews on the description of wastes and residues and the kind of phytochemicals obtained from them are also included in the special issue. Thus, the bioactive compounds present in the wastes produced during the fruit juice industry production are reviewed, updating the extraction techniques and recent valorization approaches . The bioactive compounds from honeybee production byproducts and beekeeping, the soybean processing residues, such as okara, as an excellent source of isoflavones, saponins, and fiber, focusing on the extraction methods and pharmacotherapeutic effects, and the grape winemaking residues from different cultivars are also described.…”
mentioning
confidence: 99%